An Analysis of Students’ English Book Entitled “Bahasa Inggris” from Character Education’s Point of View - Vania, Askardia Myra; Sugirin, Sugirin (International Journal of Contemporary Studies in Education, 2024)
The important of education today is in line with the explosions of technology used by the students. A lot of students now days using web browser such as: Google Chrome, Mozilla Firefox, Opera Mini, Internet explorer, and others. Cannot deny that those web browser is concern to have data that cannot be responsibility. Thus, make a student have bad behavior which is they did not really understand about the material then just copied into the assignments which can make student lost their characteristic in education. There are 18 characteristics of education mold in the role of Ministry of Education and culture like: religiosity, honesty, tolerance, discipline, hard work, creativity, independence, democracy, curiosity, sense of nationalism, patriotism, achievement orientation, communicative, love and peace, the foundation of reading, environmental awareness, social care, and responsibility. Those character education should be owned by the students while the learning process occur (with using English book to deliver the materials) as their advantages in the future called personality. With the strong character/personality, students are able to catch their dream easily. English textbook plays an important role in building students character education in learning process because it provides relevant materials in each chapter. Farther, the researcher decided to have a study to analyze the existing of English textbook entitled “Bahasa Inggris” for 10th grade of Senior High School in learning process as the implementation of those 18 characters of education in Indonesia.